2015
DOI: 10.1002/jhet.2570
|View full text |Cite
|
Sign up to set email alerts
|

Efficient One‐Pot Synthesis of Quinazoline and Benzopyrano[2,3‐d]pyrimidine Derivatives Catalyzed by N‐Bromosulfonamides

Abstract: N,N,N',N'‐tetrabromobenzene‐1,3‐disulfonamide and poly(N,N’‐dibromo‐N‐ethyl‐benzene‐1,3‐disulfonamide) were used as efficient catalysts for one‐pot synthesis of new quinazoline derivatives from various aldehydes, 2‐amino‐benzophenone, and ammonium acetate in good to excellent yields and new benzopyrano[2,3‐d]pyrimidine derivatives from salicylic aldehydes, various cyclic amines, and malononitrile in good to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…At this stage, we speculate that the intermediate 3 reacts with the ammonium acetate to form intermediate 4 . Finally, it was observed that cyclization and aromatization of intermediate 5 results in the final product 6 (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, we speculate that the intermediate 3 reacts with the ammonium acetate to form intermediate 4 . Finally, it was observed that cyclization and aromatization of intermediate 5 results in the final product 6 (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, some routes have been already reported that we review them here. Three‐component reaction catalyzed by polyphosphate ethyl ester (PPE), palladium, TBBDA, copper 1‐methylimidazolium triflouroacetate ([Hmim]TFA), butylmethylimidazolium tetrachloroferrate (bmim[FeCl 4 ]), Fe 3 O 4 /SBA‐15, CoFe 2 O 4 @B 2 O 3 ‐SiO 2 , Fe 3 O 4 @SiO 2 @TiO 2 ‐OSO 3 H, and acetic acid provide the synthesis of various quinazoline and dihydroquinazolinone derivatives. The methods reviewed above have some disadvantages such as long reaction times, by products, low product efficiency and expensive or poisonous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…26 The anti-coagulant and anti-HIV, 27 anti-histaminic, anti-microbial, 28 anti-cancer and anti-tuberculosis 29 activities of benzopyranes have been demonstrated. The presence of two backbones of pyrimidines and benzopyran in benzopyranopyrimidines has induced biological properties such as anti-inflammatory and analgesic 30 to this group of compounds. Benzopyrano[2,3- d ]pyrimidines were developed by O'Callaghan from the condensation reaction of 2-iminocoumarin-3-carboxamide with aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the application and frequent presence of structure of qunazoline in immensely important drugs such as Prazosin, Gefitinib and Erlotinib that they are used as an anticancer drug (Figure 2) has led scientists to call this structure pharmaceutical skeleton. As a matter of fact, choosing this name describes the importance of its synthesis [1][2][3][4][5][6][7][8][9][10]. The fact that presence of catalyst in chemical reaction is important is obvious to all.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, different strategies have been proposed for the synthesis of quinazoline. In 2015, Ghorbani-Vaghei et al the quinazoline derivatives were synthesized using TBBDA and PBBS catalysts[8]. Deshmukh et al in 2018 were able to synthesize quinazoline derivatives using benzylamine, ammonium acetate and 2-aminobenzylalcohol[2].…”
mentioning
confidence: 99%